A ironia como produção de humor e crítica social : uma análise pragmática das tiras de Mafalda - Oliveira, Mônica Lopes Smiderle de (2008)
This dissertation aims to analyze the humor and the irony conveyed through Mafalda’s language, Quino’s comic strips personage. Setting out from the notion of irony as a statement of something different from what one wishes to communicate, in which the emitter lets a hint of a contrary statement by the situational context or by the intonation, and observing the three Pragmatic theories: the conversational maxims of the Cooperative Principle (Grice, 1975), the Relevance theory (Sperber e Wilson, 1986, 2005) and Speech Acts theory (Austin 1990, e Searle 1969), to analyse sixteen comic strips, protagonized by Mafalda, to show how the irony strategic produces humor and social critique.